(-8n+8)+8(-n+1)=

Simple and best practice solution for (-8n+8)+8(-n+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8n+8)+8(-n+1)= equation:


Simplifying
(-8n + 8) + 8(-1n + 1) = 0

Reorder the terms:
(8 + -8n) + 8(-1n + 1) = 0

Remove parenthesis around (8 + -8n)
8 + -8n + 8(-1n + 1) = 0

Reorder the terms:
8 + -8n + 8(1 + -1n) = 0
8 + -8n + (1 * 8 + -1n * 8) = 0
8 + -8n + (8 + -8n) = 0

Reorder the terms:
8 + 8 + -8n + -8n = 0

Combine like terms: 8 + 8 = 16
16 + -8n + -8n = 0

Combine like terms: -8n + -8n = -16n
16 + -16n = 0

Solving
16 + -16n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + -16n = 0 + -16

Combine like terms: 16 + -16 = 0
0 + -16n = 0 + -16
-16n = 0 + -16

Combine like terms: 0 + -16 = -16
-16n = -16

Divide each side by '-16'.
n = 1

Simplifying
n = 1

See similar equations:

| 8h=16h | | 72in=yd | | 2z+1y+2x=3z+2y | | 4(1/3+1/3+1/3)= | | 3x^8-6x^4/3x^4 | | 52+N-7=14 | | 11-2z= | | 7t-2=-12+9t | | (x+3)(2x^2+5x+2)= | | -4(-2x+5)+(-6x+8)= | | 3z+2y=2z+1y+2x | | 8x^2+9x=5 | | h=-16t^2-19t+150 | | 3x+2y=2x+1y+2z | | 9n-19=-3+n | | 6*x^2+90x=-300 | | x+5+8(x+2)= | | h=-16t^2+5+15 | | 5[n-(m+1)]= | | x^2+12x-40= | | 2a+18=7a | | Log(9)-log(x-5)=log(45) | | 7+3n=5n+13 | | 3y+7=10 | | 3s+3=2s+10 | | 40=8-17k | | -4(-2x+3)+(-6x+8)= | | 5(x+2)+6= | | 307+x=451 | | 0.9*4= | | -7x-18=-158 | | 0.9+4= |

Equations solver categories